Enhanced electrochemical performance of hybrid composite microstructure of CuCo2O4 microflowers-NiO nanosheets on 3D Ni foam as positive electrode for stable hybrid supercapacitors. Issue 2 (15th January 2023) - Maile, Nagesh; Shinde, Surendra; Lim, Youngsu; Kim, Bolam; Ghani, Ahsan Abdul; Tahir, Khurram; Hussain, Muzammil; Jang, Jiseon; Lee, Dae Sung
Abstract: Self-assembled composite porous structures comprising CuCo2 O4 microflowers and NiO hexagonal nanosheets were synthesized on a conducting 3D Ni foam surface [CCO/NO] using a simple hydrothermal method. This unique composite assembly was further characterized and electrochemically evaluated as a binder-free positive electrode for hybrid supercapacitor application. The study showed that the CCO/NO exhibited a maximum areal capacitance of 1444 mF cm −2, significantly higher than the parent CuCo2 O4 and NiO electrodes, with remarkable stability of 88.5% for 10, 000 galvanostatic charge-discharge cycles. Key features for the enhanced electrochemical performance of CCO/NO can be related to a lowered diffusion resistance because the hybrid nanocomposite porous assembly generates short diffusion paths for electrolyte ions and more active sites for reversible faradaic transition for charge storage. The hybrid supercapacitor was assembled using activated carbon as a negative electrode and CCO/NO as a positive electrode in alkaline electrolyte, performed at an improved potential of 1.6 V. Device showed a maximum areal capacitance of 122 mF cm −2, a maximum areal energy density of 43 μWh cm −2, and a maximum areal power density of 5.1 mW cm −2 . This hybrid supercapacitor showed remarkable cyclic stability up to 98% for 10, 000 cycles. This study encourages the development of low-cost, high-performance, durable electrode designs using hybrid composite for next-generation energy storage systems.